A nanocomposite coating and a method for preparing an initial substrate surface film layer for a single-piece non-insulating fireproof glass

By applying nanocomposite coating on a single piece of non-thermal insulation fire-resistant glass, the problem of limited vulnerability and light transmission performance of traditional fire-resistant glass at high temperatures is solved, and higher fire integrity time and light transmission are achieved.

CN119529571BActive Publication Date: 2025-04-18SICHUAN POLYFILL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510096675.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-18
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Traditional multi-layer composite fireproof glass has high manufacturing costs, weight burden and limited light transmission performance, especially in extreme high temperature environments, which are extremely vulnerable and difficult to widely use.

Method used

The nanocomposite coating is adopted to improve the toughness and impact strength of the glass through the synergistic effect of nanocomposite oxides, toughening materials and glass molten liquid, extend the fire resistance integrity time, and maintain high light transmittance and ultraviolet radiation resistance.

Benefits of technology

It achieves fire-resistant performance that maintains the structure stability at high temperatures and blocks flame and heat propagation, and has good impact, scratch and wear resistance, while meeting the demand for glass lighting in the construction field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of fireproof glass, and in particular to a nanocomposite coating, and a method for preparing the initial substrate surface film layer for a monolithic non-insulating fireproof glass, wherein the nanocomposite coating is prepared from the following raw materials in parts by weight: 50-80 parts of nanocomposite oxide, 10-15 parts of toughening material, 15-30 parts of glass melt, and 1-5 parts of flux; preparation method: S1, using flux as a medium, mixing the nanocomposite oxide with the toughening material, grinding for 1-2 hours, then adding glass melt thereto, continuously grinding for 2-3 hours, then heating to 180-220°C, heat treatment, removing the flux, and obtaining a nanocomposite; S2, depositing on the surface of a glass substrate by physical vapor deposition or chemical vapor deposition to form a nanocomposite coating. The nanocomposite coating of the method improves the toughness and impact strength of the glass, prolongs its fireproof integrity time, and also has better light transmittance and ultraviolet radiation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fireproof glass, in particular to a nano composite material coating and a method for preparing an initial substrate surface film layer for a single piece of non-insulating fireproof glass. Background Art

[0002] As urbanization progresses at an increasingly rapid pace, the building windows of houses are becoming larger and larger. Elegant, beautiful, functional and safe glass components are gradually gaining favor among designers at home and abroad, which directly leads to the rapid development of various types of safety glass and special glass in the architectural glass industry. Architectural glass has gradually developed from being a simple lighting and decorative material to having multiple functions such as light control, room temperature regulation, noise reduction, and improvement of living environment. In addition to some properties of ordinary glass, fireproof glass also has the properties of controlling the spread of fire, smoke isolation and heat insulation, which provides precious rescue time for effective rescue in the event of a fire and minimizes the loss of personnel, property and buildings. Fireproof glass can protect escape and rescue personnel from heat radiation damage and reduce the destructive power of fire to a minimum.

[0003] The Chinese invention patent with the publication (announcement) number CN118271913 provides a protective coating for coated glass and a preparation method thereof, which belongs to the technical field of glass deep processing; the coating material is sprayed on the coated surface of the coated glass and then heated and cured to form; the components of the coating material include 93% to 96% polyvinyl alcohol, 0.9% to 1.3% plasticizer, 2% to 3% adhesion enhancer and 1.6% to 2.2% enzyme preparation; wherein the plasticizer is one of ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, neopentyl glycol, glycerol, sorbitol, trimethylolpropane, diethanolamine, triethanolamine and adipic acid, the adhesion enhancer is one of polyvinyl pyrrolidone, polyethylene glycol and polycaprolactone, and the enzyme preparation is a mixture of one or more of PVA dehydrogenase, PVA oxidase and PVA hydrolase. Its function is to make the glass have the advantages of strong scratch resistance and can be removed by washing. The Chinese invention patent with publication number CN118146719A discloses a liquid ceramic thermal insulation coating and its preparation method and application. The liquid ceramic thermal insulation coating is composed of the following components in parts by weight: 15-30 parts of ceramic powder, 2-8 parts of microcrystalline glass powder, 1-10 parts of organic glass powder, 20-40 parts of adhesive, 20-40 parts of curing agent, 1-5 parts of film-forming aid, 1-5 parts of dispersant, and 1-5 parts of defoaming agent; wherein the ceramic powder is composed of heavy calcium carbonate and calcium phosphate in a mass ratio of 1: (0.5-0.8). The above-mentioned liquid ceramic thermal insulation coating mainly improves its thermal insulation effect, and its application field is the surface of factory buildings.

[0004] The performance of the above-mentioned coating materials is relatively simple, and with the continuous evolution and strengthening of building safety regulations, fireproof glass, as a key material to ensure the safety of life and property, has also been pushed to a new height in terms of performance standards. Although the traditional multi-layer composite fireproof glass system has shown certain advantages in resisting the spread of fire, its high manufacturing cost, significant weight burden and relatively limited light transmittance have become the main bottlenecks restricting its widespread application. In this context, exploring more efficient, lightweight and light-transmitting single-piece non-insulating fireproof glass solutions has become a technical problem that needs to be overcome in the field of building materials science. However, the fragility of single-piece glass materials in extremely high temperature environments is particularly prominent, and they are very prone to cracking or even falling off. For this reason, this application is dedicated to studying a nano-composite coating for the surface of a glass substrate to enhance its fire resistance, crack resistance, etc., which belongs to a coating composition. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a nanocomposite coating and a method for preparing an initial substrate surface film layer for a single-piece non-insulating fireproof glass. The nanocomposite coating of the method improves the toughness and impact strength of the glass, prolongs its fire-resistant integrity time, and also has better light transmittance and ultraviolet radiation resistance.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A nano composite material coating is prepared from the following raw materials in parts by weight: 50-80 parts of nano composite oxide, 10-15 parts of toughening material, 15-30 parts of glass melt and 1-5 parts of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 75-80:3-5:10-15; the toughening material is nano silicon dioxide; the glass melt is prepared from 15-20 parts of borosilicate, 5-10 parts of borate and 15-20 parts of glass fiber; and the flux is modified acrylic acid.

[0008] The above-mentioned nanocomposite coating forms a layer of protection on the surface of a single piece of non-insulating fireproof glass. Among them, the nanocomposite oxide itself has a high thermal stability and can prevent the rapid transfer of flames and heat in a high temperature environment. When encountering a fire, this film can slow down the temperature rise rate of the glass substrate, effectively maintain the integrity of the glass, and extend its fire resistance time. Adding toughening materials can prevent the glass from cracking or breaking due to thermal stress at high temperatures. During the heating process, the toughening material can absorb part of the energy and enhance the overall toughness of the glass, so that the glass can withstand higher temperatures and thermal shocks, effectively preventing the generation of cracks, thereby improving the fireproof performance. At the same time, the nanocomposite coating is closely combined with the glass substrate and can enhance the hardness of the glass surface. The synergistic effect of the nanocomposite oxide and the toughening material can make the glass surface more wear-resistant and scratch-resistant. During the transportation, installation and daily use of the glass, surface damage can be reduced and the appearance and performance of the glass can be maintained.

[0009] The nanocomposite oxide and the toughening material are in contact with each other and tightly combined during the preparation process. The toughening material can fill the gaps between the nanocomposite oxide particles to form an interlocking structure. This structure enhances the interfacial bonding force inside the nanocomposite coating, making the entire film layer stronger. In a high temperature environment, this tight interfacial bonding can prevent delamination inside the material layer, thereby ensuring the integrity of the film layer during the fire protection process.

[0010] The glass melt acts as a binder in the nanocomposite coating. It can better fuse the nanocomposite oxide particles together, and during the coating process, the nanocomposite oxide can be evenly distributed on the surface of the glass substrate. At the same time, after cooling, the glass melt can form a whole with the nanocomposite oxide, which enhances the adhesion between the nanocomposite coating and the glass substrate. Moreover, the glass melt itself also has a certain glassy structure, which can work together with the nanocomposite oxide to enhance the thermal stability and mechanical properties of the film layer.

[0011] The flux acts as a medium in the grinding process. At a lower temperature (80-90°C), the flux can reduce the friction between the nanocomposite oxide and the toughening material, allowing them to be ground and mixed more effectively. The flux can help the nanocomposite oxide and the toughening material to disperse better and avoid agglomeration, thereby ensuring the uniformity of the subsequent materials.

[0012] In the nanocomposite coating, nanocomposite oxide and toughening material are the main functional components, providing high thermal stability and a certain hardness. At high temperatures, the nanocomposite oxide can form a stable structure to prevent the rapid transfer of heat. The toughening material is tightly combined with the nanocomposite oxide, and its molecular chains or particles can be filled in the gaps of the nanocomposite oxide. When the glass is subjected to thermal stress or external force impact, the toughening material can absorb energy through its own deformation, effectively disperse the impact force, and reduce the risk of glass breakage.

[0013] Preferably, the modified acrylic acid is prepared by copolymerizing acrylic acid and acrylate monomers.

[0014] Preferably, the method for preparing the modified acrylic acid comprises the following steps:

[0015] (1) Add acrylic acid to deionized water and stir evenly. Add composite emulsifier under nitrogen atmosphere, continue stirring and heat to 40-60°C, add ammonium persulfate, keep stirring for 15-25 minutes, add acrylate monomer dropwise within 5-7 hours, continue stirring and reacting for 2-5 hours, and then cool to below 30°C;

[0016] (2) The reaction solution obtained in step (1) is adjusted to a pH of 7-8 with a pH adjuster, then filtered and washed until the pH of the filtrate is 7, and the obtained powder is dried to obtain modified acrylic acid.

[0017] Preferably, the mass ratio of acrylic acid, acrylate monomer, composite emulsifier and ammonium persulfate in step (1) is: 60-80: 8-14: 1.5-4.5: 0.4-0.9.

[0018] Preferably, the acrylic acid ester monomers in step (1) are composed of methyl acrylate, butyl acrylate and butyl methacrylate, wherein the mass ratio of methyl acrylate:butyl acrylate:butyl methacrylate is 7-9:20-30:5-7.

[0019] Preferably, the composite emulsifier in step (1) is composed of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate and nonylphenol polyoxyethylene ether alcohol, and the mass ratio of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate and nonylphenol polyoxyethylene ether in the composite emulsifier is 1:0.8-1.2:0.9-1.3.

[0020] The nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide. Due to its small particle size, it is easy to agglomerate. The modified acrylic flux prepared by copolymerization of acrylic acid and acrylate monomers contains abundant polar groups such as carboxyl on its molecular chain. These polar groups can interact with metal ions or oxygen ions on the surface of the nano composite oxide, such as forming coordination bonds or electrostatic adsorption. This interaction can effectively prevent the agglomeration of nano composite oxide particles, so that they can be evenly dispersed in the system during grinding and mixing.

[0021] Glass melt is prepared from borosilicate, borate and glass fiber, and its properties such as viscosity and surface tension will affect the fusion with other materials. Modified acrylic flux can reduce the viscosity and surface tension of glass melt, making it easier for materials such as nano-composite oxides and nano-silicon dioxide to blend into the glass melt. During the mixing process, the molecular chain of the modified acrylic flux can act as a "bridge" between the glass melt and other materials, promote the full fusion between the materials, form a uniform mixing system, and ensure the quality and performance uniformity of the nano-composite coating.

[0022] Acrylic acid monomer alone will lead to high viscosity in the system, affecting the processing and use performance of the material. However, the molecular structure of modified acrylic acid after copolymerization with acrylate monomer has changed, which can effectively reduce the viscosity of the system, making the material easier to mix and operate during the preparation process, and improving production efficiency. In addition, the thermal stability of pure acrylic acid monomer is relatively poor, and decomposition or cross-linking reactions may occur under high temperature conditions, affecting the performance of the flux. Since the acrylate monomer is introduced into the molecular structure of the modified acrylic acid, its thermal stability is improved, and it can maintain good stability under high temperature environment, thereby ensuring that the flux can play a better role in the preparation process of the nanocomposite coating. In addition, the modified acrylic acid flux has better compatibility with raw materials such as nanocomposite oxides and toughening materials, and can be better dispersed in the system, promote the interaction between the raw materials, and form a uniform material system. However, the compatibility of acrylic acid monomer with some of the raw material components is poor, and it is easy to have problems such as phase separation, which affects the overall performance of the material.

[0023] A method for preparing a surface film layer of an initial substrate for a single piece of non-insulating fireproof glass, wherein the nanocomposite coating, a silver film layer and a nickel alloy film layer are sequentially formed on the surface of the initial substrate for the single piece of non-insulating fireproof glass;

[0024] The preparation method of the nanocomposite coating is as follows:

[0025] S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 80-90°C at a rate of 300-500 r / min for 1-2 hours, adding glass melt thereto, grinding for 2-3 hours, heating to 180-220°C, heat-treating the mixture, removing the flux, and obtaining a nanocomposite material;

[0026] S2, depositing the nanocomposite material on the surface of the glass substrate by physical vapor deposition or chemical vapor deposition to form a nanocomposite material coating.

[0027] Preferably, the thickness of the silver film layer is 8-10 nm.

[0028] Preferably, the nanocomposite coating, the silver film layer and the nickel alloy film layer are all formed by vacuum ion sputtering.

[0029] Preferably, the nickel alloy film layer comprises the following components in parts by weight: 81-89 parts of Ni, 4-11 parts of Cr, 3-7 parts of Fe, 2-10 parts of Cu and 0.5-2 parts of Mg.

[0030] The vacuum ion sputtering method can form a uniform and dense nanocomposite coating on the surface of the substrate, avoiding defects such as pores and cracks that may occur in traditional coating methods, improving the bonding strength between the coating and the substrate, and enabling the coating to better exert its protective and functional characteristics. In a vacuum environment, ions are used to bombard the silver target material, causing silver atoms to sputter and deposit on the surface of the substrate to form a coating. This method can prevent silver from reacting with impurities such as oxygen in the air, thereby obtaining a high-purity, uniform and dense silver coating structure. Silver atoms have high energy and can form a good bond with the substrate when they hit the substrate surface, making the adhesion between the silver coating and the substrate strong, and not prone to peeling and falling off, thereby improving the stability and durability of the coating.

[0031] Vacuum ion sputtering can evenly sputter various alloy elements from the nickel alloy target and deposit them on the substrate surface to form a coating with uniform composition. This helps to ensure the performance consistency of the nickel alloy coating, so that it exhibits stable performance in terms of corrosion resistance, wear resistance, high temperature resistance, etc. The nickel alloy layer has a high proportion of nickel, and the melting point of nickel is 1453℃, which enables the nickel alloy film layer to maintain a relatively stable solid structure under high temperature environment. When a fire occurs, the nickel alloy film layer can act as a thermal barrier to effectively slow down the transfer of heat to the inside of the glass. The heat of the flame needs to heat up, melt or decompose the nickel alloy film layer before it can further affect the glass. This process consumes a lot of heat and takes time, thereby providing certain fire protection for the glass. The chromium (Cr) in the alloy can form a dense chromium oxide protective film on the surface of the alloy. In a high temperature and oxygen-rich fire environment, this protective film can prevent oxygen from further oxidizing the metal inside the alloy and maintain the structural integrity of the nickel alloy film layer. This anti-oxidation property ensures that the nickel alloy film layer can continue to function as a thermal barrier at high temperatures and will not fail quickly due to oxidation, thereby enhancing its fire resistance.

[0032] The present invention has the following beneficial effects:

[0033] The present invention sets a nanocomposite coating on the surface of a monolithic non-insulating fireproof glass substrate, wherein the nanocomposite oxide provides fireproofing and partial mechanical performance enhancement, the toughening material improves the impact resistance and thermal shock resistance, the glass melt plays a role of bonding and forming, and the glass melt itself also has a certain glass structure, which can work with the nanocomposite oxide to enhance the thermal stability and mechanical properties of the film layer. The synergistic effect of the three makes the prepared nanocomposite coating maintain structural stability at high temperatures in terms of fireproofing performance, effectively blocking the spread of flames and heat; in terms of mechanical properties, it has good impact resistance, scratch resistance and wear resistance; in terms of optical properties, it maintains a high light transmittance to meet the needs of glass lighting in the fields of construction and so on.

[0034] Furthermore, a silver film layer and a nickel alloy film layer are arranged on the surface of the nanocomposite coating, which can work in coordination with the nanocomposite coating to enhance the fireproof performance. When the flame heat is transferred to the glass surface, the nickel alloy film layer first plays a preliminary barrier role. On this basis, the silver film layer and the nanocomposite coating further block the penetration of heat to form a double-layer protection system. This synergistic effect can greatly extend the fire resistance time of glass in a fire, effectively prevent the damage of flames and heat to the glass, and maintain the integrity of the glass. At the same time, the silver film layer can effectively reflect the infrared heat radiation in the room, reduce the loss of indoor heat to the outside in winter, and block the outdoor heat from entering the room in summer, greatly reducing the energy consumption of the building and improving the energy efficiency. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application. The raw materials used in the following embodiments are all common commercially available products.

[0036] Example 1

[0037] A nano composite material coating is prepared from the following raw materials in parts by weight: 65 parts of nano composite oxide, 12 parts of toughening material, 22 parts of glass melt, and 3 parts of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 77:4:12; the toughening material is nano silicon dioxide; the glass melt is prepared from 18 parts of borosilicate, 8 parts of borate and 17 parts of glass fiber; and the flux is modified acrylic acid.

[0038] The modified acrylic acid is prepared by copolymerization of acrylic acid and acrylate monomers, and the modified acrylic acid is prepared from the following raw materials in parts by weight:

[0039] 70 parts of acrylic acid, 11 parts of acrylate monomer, 3 parts of composite emulsifier, and 0.6 parts of ammonium persulfate. The acrylate monomer is composed of methyl acrylate, butyl acrylate, and butyl methacrylate, and the mass ratio of methyl acrylate: butyl acrylate: butyl methacrylate is 8:25:6. The composite emulsifier is composed of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether, and the mass ratio of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether is 1:1:1.

[0040] The preparation method of the modified acrylic acid comprises the following steps:

[0041] (1) First, add 120 parts of deionized water to the reaction tank, then add acrylic acid, stir evenly, then add the composite emulsifier under nitrogen atmosphere, continue stirring and heat to 50°C, add ammonium persulfate, keep stirring for 20 minutes, then drop the acrylic acid monomer within 6 hours, keep stirring and nitrogen protection, continue stirring and react for 3 hours after the addition is complete, and cool to below 30°C after the reaction is complete;

[0042] (2) The reaction solution obtained in step (1) was adjusted to a pH of 9-10 with an aqueous sodium carbonate solution, and the stirring was continued for 10 min. The pH was then adjusted to 7-8 with an aqueous HCl solution, and the solution was filtered and washed until the pH of the filtrate was 7. The powder was dried in a vacuum drying oven at 120° C. to a constant weight to obtain modified acrylic acid.

[0043] A method for preparing an initial substrate surface film layer for a single-piece non-insulating fireproof glass, specifically comprising:

[0044] The first step is to pre-treat the initial substrate and then provide the above-mentioned nanocomposite coating on its surface;

[0045] The second step is to form a silver film layer by vacuum ion sputtering deposition on the outside of the nanocomposite coating, wherein the thickness of the silver film layer is 8 nm;

[0046] The third step is to deposit a nickel alloy film layer on the outside of the silver coating by vacuum ion sputtering, wherein the nickel alloy film layer includes the following components by weight: 85 parts of Ni, 8 parts of Cr, 5 parts of Fe, 5 parts of Cu and 1.2 parts of Mg, to obtain a single piece of non-insulating fireproof glass.

[0047] In the first step, the method for preparing the nanocomposite coating comprises the following steps:

[0048] S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 85°C at a rate of 400 r / min for 1.5 hours, adding glass melt thereto, grinding for 2.5 hours, heating to 200°C, heat-treating the mixture, removing the flux, and obtaining a nanocomposite material;

[0049] S2, depositing the nanocomposite material on the surface of the glass substrate by vacuum ion sputtering to form a nanocomposite material coating.

[0050] Example 2

[0051] A nano composite material coating is prepared from the following raw materials in parts by weight: 80 parts of nano composite oxide, 10 parts of toughening material, 25 parts of glass melt, and 1 part of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 80:3:10; the toughening material is nano silicon dioxide; the glass melt is prepared from 15 parts of borosilicate, 10 parts of borate and 18 parts of glass fiber; and the flux is modified acrylic acid.

[0052] Modified acrylic acid is made from the following raw materials in parts by weight:

[0053] 60 parts of acrylic acid, 14 parts of acrylate monomer, 4.5 parts of composite emulsifier, and 0.4 parts of ammonium persulfate. The acrylate monomer is composed of methyl acrylate, butyl acrylate, and butyl methacrylate, and the mass ratio of methyl acrylate: butyl acrylate: butyl methacrylate is 9:20:7. The composite emulsifier is composed of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether, and the mass ratio of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether is 1:0.8:1.3.

[0054] The modified acrylic acid is prepared by copolymerizing acrylic acid and acrylate monomers. The preparation method of the modified acrylic acid comprises the following steps:

[0055] (1) First, add 100 parts of deionized water to the reaction tank, then add acrylic acid, stir evenly, then add the composite emulsifier under nitrogen atmosphere, continue stirring and heat to 40°C, add ammonium persulfate, keep stirring for 25 minutes, then drop the acrylic acid ester monomer within 5 hours, keep stirring and nitrogen protection, continue stirring and react for 5 hours after the addition is complete, and cool to below 30°C after the reaction is complete;

[0056] (2) The reaction solution obtained in step (1) was adjusted to a pH of 9-10 with an aqueous sodium carbonate solution, and the stirring was continued for 10 min. The pH was then adjusted to 7-8 with an aqueous HCl solution, and the solution was filtered and washed until the pH of the filtrate was 7. The powder was dried in a vacuum drying oven at 120° C. to a constant weight to obtain modified acrylic acid.

[0057] The method for preparing the surface film layer of the initial substrate for a single piece of non-insulating fireproof glass is specifically as follows:

[0058] The first step is to pre-treat the initial substrate and then provide the above-mentioned nanocomposite coating on its surface;

[0059] The second step is to form a silver film layer by vacuum ion sputtering deposition on the outside of the nanocomposite coating, wherein the thickness of the silver film layer is 10 nm;

[0060] The third step is to deposit a nickel alloy film layer on the outside of the silver coating by vacuum ion sputtering, wherein the nickel alloy film layer includes the following components in parts by weight: 89 parts of Ni, 11 parts of Cr, 3 parts of Fe, 8 parts of Cu and 0.5 parts of Mg, to obtain a single piece of non-insulating fireproof glass.

[0061] The preparation method of the nanocomposite coating comprises the following steps:

[0062] S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 80°C at a rate of 500 r / min for 2 hours, adding glass melt thereto, grinding for 2.8 hours, heating to 180°C, heat-treating the mixture, removing the flux, and obtaining a nanocomposite material;

[0063] S2, depositing the nanocomposite material on the surface of the glass substrate by vacuum ion sputtering to form a nanocomposite material coating.

[0064] Example 3

[0065] A nano composite material coating is prepared from the following raw materials in parts by weight: 50 parts of nano composite oxide, 15 parts of toughening material, 30 parts of glass melt, and 5 parts of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 75:5:14; the toughening material is nano silicon dioxide; the glass melt is prepared from 20 parts of borosilicate, 5 parts of borate and 15 parts of glass fiber; and the flux is modified acrylic acid.

[0066] Modified acrylic acid is made from the following raw materials in parts by weight:

[0067] 80 parts of acrylic acid, 8 parts of acrylate monomer, 1.5 parts of composite emulsifier, and 0.9 parts of ammonium persulfate. The acrylate monomer is composed of methyl acrylate, butyl acrylate, and butyl methacrylate, and the mass ratio of methyl acrylate: butyl acrylate: butyl methacrylate is 7:30:5. The composite emulsifier is composed of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether, and the mass ratio of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether is 1:1.2:0.9.

[0068] The modified acrylic acid is prepared by copolymerizing acrylic acid and acrylate monomers. The preparation method of the modified acrylic acid comprises the following steps:

[0069] (1) First, add 150 parts of deionized water to the reaction tank, then add acrylic acid, stir evenly, then add the composite emulsifier under nitrogen atmosphere, continue stirring and heat to 60°C, add ammonium persulfate, keep stirring for 15 minutes, then drop the acrylic acid ester monomer within 7 hours, keep stirring and nitrogen protection, continue stirring and react for 2 hours after the addition is completed, and cool to below 30°C after the reaction is completed;

[0070] (2) The reaction solution obtained in step (1) was adjusted to a pH of 9-10 with an aqueous sodium carbonate solution, and the stirring was continued for 10 min. The pH was then adjusted to 7-8 with an aqueous HCl solution, and the solution was filtered and washed until the pH of the filtrate was 7. The powder was dried in a vacuum drying oven at 120° C. to a constant weight to obtain modified acrylic acid.

[0071] The method for preparing the surface film layer of the initial substrate for a single piece of non-insulating fireproof glass is specifically as follows:

[0072] The first step is to pre-treat the initial substrate and then provide the above-mentioned nanocomposite coating on its surface;

[0073] The second step is to form a silver film layer by vacuum ion sputtering deposition on the outside of the nanocomposite coating, wherein the thickness of the silver film layer is 9 nm;

[0074] The third step is to deposit a nickel alloy film layer on the outside of the silver coating by vacuum ion sputtering, wherein the nickel alloy film layer includes the following components by weight: 86 parts of Ni, 4 parts of Cr, 7 parts of Fe, 2 parts of Cu and 1.6 parts of Mg, to obtain a single piece of non-insulating fireproof glass.

[0075] The preparation method of the nanocomposite coating comprises the following steps:

[0076] S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 90°C at a rate of 300 r / min for 1 hour, then adding glass melt thereto, grinding for 2 hours, and then heating to 220°C, heat-treating the mixture to remove the flux, and obtaining a nanocomposite material;

[0077] S2, depositing the nanocomposite material on the surface of the glass substrate by physical vapor deposition to form a nanocomposite material coating.

[0078] Example 4

[0079] A nano composite material coating is prepared from the following raw materials in parts by weight: 70 parts of nano composite oxide, 14 parts of toughening material, 15 parts of glass melt, and 4 parts of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 77:3:15; the toughening material is nano silicon dioxide; the glass melt is prepared from 16 parts of borosilicate, 9 parts of borate and 20 parts of glass fiber; and the flux is modified acrylic acid.

[0080] Modified acrylic acid is made from the following raw materials in parts by weight:

[0081] 75 parts of acrylic acid, 12 parts of acrylate monomer, 3.5 parts of composite emulsifier, and 0.6 parts of ammonium persulfate. The acrylate monomer is composed of methyl acrylate, butyl acrylate, and butyl methacrylate, and the mass ratio of methyl acrylate: butyl acrylate: butyl methacrylate is 8:22:7. The composite emulsifier is composed of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether, and the mass ratio of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, and nonylphenol polyoxyethylene ether is 1:1.1:1.

[0082] The modified acrylic acid is prepared by copolymerizing acrylic acid and acrylate monomers. The preparation method of the modified acrylic acid comprises the following steps:

[0083] (1) First, add 140 parts of deionized water to the reaction tank, then add acrylic acid, stir evenly, then add the composite emulsifier under nitrogen atmosphere, continue stirring and heat to 45°C, add ammonium persulfate, keep stirring for 22 minutes, then drop the acrylic acid ester monomer within 5 hours, keep stirring and nitrogen protection, continue stirring and react for 4 hours after the addition is complete, and cool to below 30°C after the reaction is complete;

[0084] (2) The reaction solution obtained in step (1) was adjusted to a pH of 9-10 with an aqueous sodium carbonate solution, and the stirring was continued for 10 min. The pH was then adjusted to 7-8 with an aqueous HCl solution, and the solution was filtered and washed until the pH of the filtrate was 7. The powder was dried in a vacuum drying oven at 120° C. to a constant weight to obtain modified acrylic acid.

[0085] The method for preparing the surface film layer of the initial substrate for a single piece of non-insulating fireproof glass is specifically as follows:

[0086] The first step is to pre-treat the initial substrate and then provide the above-mentioned nanocomposite coating on its surface;

[0087] The second step is to form a silver film layer by vacuum ion sputtering deposition on the outside of the nanocomposite coating, wherein the thickness of the silver film layer is 9 nm;

[0088] The third step is to deposit a nickel alloy film layer on the outside of the silver coating by vacuum ion sputtering, wherein the nickel alloy film layer includes the following components by weight: 81 parts of Ni, 7 parts of Cr, 4 parts of Fe, 10 parts of Cu and 2 parts of Mg, to obtain a single piece of non-insulating fireproof glass.

[0089] The preparation method of the nanocomposite coating comprises the following steps:

[0090] S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 83°C at a rate of 460 r / min for 1.2 h, then adding glass melt thereto, grinding for 3 h, and then heating to 190°C, heat-treating the mixture to remove the flux, and obtaining a nanocomposite material;

[0091] S2, depositing the nanocomposite material on the surface of the glass substrate by chemical vapor deposition to form a nanocomposite material coating.

[0092] Comparative Example 1

[0093] A nano composite material coating is prepared by uniformly mixing nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 77:4:12, and the rest is the same as in Example 1. The preparation method of the initial substrate surface film layer for a single non-insulating fireproof glass is the same as in Example 1.

[0094] Comparative Example 2

[0095] A nano composite material coating is prepared from the following raw materials in parts by weight: 65 parts of nano composite oxide, 12 parts of toughening material, 22 parts of glass melt, and 3 parts of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 77:4:12; the toughening material is nano silicon dioxide; the glass melt is prepared from 18 parts of borosilicate, 8 parts of borate and 17 parts of glass fiber; and the flux is acrylic acid.

[0096] The preparation method of the nanocomposite coating comprises the following steps:

[0097] S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 85°C at a rate of 400 r / min for 1.5 hours, adding glass melt thereto, grinding for 2.5 hours, heating to 200°C, heat-treating the mixture, removing the flux, and obtaining a nanocomposite material;

[0098] S2, depositing the nanocomposite material on the surface of the glass substrate by physical vapor deposition to form a nanocomposite material coating.

[0099] The rest is the same as in Example 1.

[0100] Performance Testing:

[0101] According to the fire resistance test method for glass-mounted components in GB / T 12513-2006, a fire resistance test was conducted on the single-piece non-insulating fireproof glass provided in Examples 1-4 and Comparative Examples 1-2. Six parallel samples were taken for the experiment, and the average value of the data was taken as the experimental result.

[0102] The ultraviolet radiation resistance and light transmittance of the single-piece non-insulating fireproof glass provided in the above-mentioned Examples 1-4 and Comparative Examples 1-2 were tested by the testing methods of the national standards GB∕T5137.3-2002 and GB / T 15763.1-2009.

[0103] The specific test data is shown in Table 1.

[0104] Table 1. Performance parameters of single-piece non-insulating fire-resistant glass

[0105]

[0106] As can be seen from Table 1, the fire-resistant integrity time of the single-piece non-insulating fire-resistant glass obtained by the preparation method of Examples 1-4 of the present invention is more than 3 hours, while the fire-resistant integrity time of the single-piece non-insulating fire-resistant glass of Comparative Examples 1 and 2 is only 140 and 150 minutes, both less than 3 hours, and the light transmittance and ultraviolet radiation resistance of Examples 1-4 are also better than those of Comparative Examples 1 and 2. It can be seen that the use of the nanocomposite coating of the present invention improves the toughness and impact strength of the glass, prolongs its fire-resistant integrity time, and also has better light transmittance and ultraviolet radiation resistance.

[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0108] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A nanocomposite coating, characterized in that: The invention is prepared from the following raw materials in parts by weight: 50-80 parts of nano composite oxide, 10-15 parts of toughening material, 15-30 parts of glass melt, and 1-5 parts of flux; the nano composite oxide is a mixture of nano cuprous oxide, nano nickel oxide and nano manganese dioxide in a mass ratio of 75-80:3-5:10-15; the toughening material is nano silicon dioxide; the glass melt is prepared from 15-20 parts of borosilicate, 5-10 parts of borate and 15-20 parts of glass fiber; the flux is modified acrylic acid; The modified acrylic acid is prepared by copolymerizing acrylic acid and acrylate monomers; The preparation method of the modified acrylic acid comprises the following steps: (1) Add acrylic acid to deionized water and stir evenly. Add composite emulsifier under nitrogen atmosphere, continue stirring and heat to 40-60°C, add ammonium persulfate, keep stirring for 15-25 minutes, add acrylate monomer dropwise within 5-7 hours, continue stirring and reacting for 2-5 hours, and then cool to below 30°C; (2) The reaction solution obtained in step (1) is adjusted to a pH of 7-8 with a pH adjusting agent, then filtered and washed until the pH of the filtrate is 7, and the obtained powder is dried to obtain modified acrylic acid; The mass ratio of acrylic acid, acrylate monomer, composite emulsifier and ammonium persulfate in step (1) is: 60-80: 8-14: 1.5-4.5: 0.4-0.9; The acrylic acid ester monomers in step (1) are composed of methyl acrylate, butyl acrylate and butyl methacrylate, wherein the mass ratio of methyl acrylate:butyl acrylate:butyl methacrylate is 7-9:20-30:5-7.

2. The nanocomposite coating according to claim 1, characterized in that: The composite emulsifier in step (1) is composed of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate and nonylphenol polyoxyethylene ether alcohol, and the mass ratio of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate and nonylphenol polyoxyethylene ether in the composite emulsifier is 1:0.8-1.2:0.9-1.

3.

3. A method for preparing a surface film layer of an initial substrate for a single-piece non-insulating fireproof glass, characterized in that: Sequentially forming a nanocomposite coating layer, a silver film layer and a nickel alloy film layer as claimed in any one of claims 1 to 2 on the surface of an initial substrate for a single non-insulating fireproof glass; The preparation method of the nanocomposite coating is as follows: S1, using flux as a medium, grinding the nanocomposite oxide and the toughening material at 80-90°C at a rate of 300-500 r / min for 1-2 hours, adding glass melt thereto, grinding for 2-3 hours, heating to 180-220°C, heat-treating the mixture, removing the flux, and obtaining a nanocomposite material; S2, depositing the nanocomposite material on the surface of the glass substrate by physical vapor deposition or chemical vapor deposition to form a nanocomposite material coating.

4. The method for preparing the initial substrate surface film layer for the monolithic non-insulating fireproof glass according to claim 3, characterized in that: The thickness of the silver film layer is 8-10 nm.

5. The method for preparing the initial substrate surface film layer for the monolithic non-insulating fireproof glass according to claim 3, characterized in that: The nano composite material coating, the silver film layer and the nickel alloy film layer are all formed by vacuum ion sputtering.

6. The method for preparing the initial substrate surface film layer for the monolithic non-insulating fireproof glass according to claim 3, characterized in that: The nickel alloy film layer comprises the following components by weight: 81-89 parts of Ni, 4-11 parts of Cr, 3-7 parts of Fe, 2-10 parts of Cu and 0.5-2 parts of Mg.

Citation Information

Patent Citations

  • Liquid ceramic thermal insulation coating as well as preparation method and application thereof

    CN118146719A

  • Coated glass substrate or glass ceramic substrate with resistant multi-functional surface properties, method for production thereof and use thereof

    CN107074621A

  • High-adhesion water-based ink and preparation method thereof

    CN111534149A